Creativity of Madrasah Principals in Developing Innovation of State Madrasah Aliyah Teachers in Riau Islands Province - Rita Sahara Munte; Kasful Anwar Us; Kemas Imron Rosadi; Isropil Siregar (International Journal of Interdisciplinary Research, 2025)
This paper explores the role of madrasah principals in fostering creativity and innovation among teachers at State Madrasah Aliyah in the Riau Islands Province. Through a qualitative research design, in-depth interviews and classroom observations were conducted with 15 principals and 30 teachers to examine the leadership strategies employed by principals in promoting innovative teaching practices. The study highlights the multifaceted approach of madrasah principals, encompassing professional development, collaborative teaching practices, and the integration of modern educational technologies to stimulate creativity among educators. Findings suggest that madrasah principals who emphasize continuous learning, open communication, and a culture of experimentation contribute significantly to the innovative capacity of teachers. Additionally, this research draws on Islamic educational values, referencing Qur’anic teachings and Hadith to provide a theoretical framework for leadership and creativity in Islamic educational settings. The study contributes to the growing body of literature on educational leadership within Islamic institutions, offering practical insights into how leadership can enhance the quality of teaching and learning in madrasahs. The implications of these findings are discussed, with recommendations for policy and practice to further cultivate an environment conducive to creativity and innovation in madrasah education.